2016
DOI: 10.5507/bp.2015.048
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal comorbidities in patients with psoriasis in the Czech Republic: The results of 189 patients with psoriasis and 378 controls

Abstract: Aims. The aim of the study was to investigate gastrointestinal comorbidities, identify risk factors and detect the early stages of autoimmune gastrointestinal diseases, such as Crohn's disease, ulcerative colitis and coeliac disease in patients with psoriasis. Methods. This was a hospital-based case-control study. Patients with chronic plaque psoriasis were included as cases. The control group consisted of patients with other skin diseases and who complied with the same selection criteria as cases. Two control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Other dermatological diseases, such as psoriasis, vitiligo, and alopecia areata, are diagnosed before CD. Interestingly, benefits of a gluten-free diet have been described (26) in these diseases, although the cause is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Other dermatological diseases, such as psoriasis, vitiligo, and alopecia areata, are diagnosed before CD. Interestingly, benefits of a gluten-free diet have been described (26) in these diseases, although the cause is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that the risk of CD and UC during the course of psoriasis is more than twofold and nearly twice higher than in the general population, respectively, also after exclusion of patients treated with anti-TNF agents [ 30 ]. Furthermore, some studies demonstrated that despite the lack of clinical abnormalities, psoriatic patients may present with microscopic evidence of intestinal inflammation and elevated levels of pANCA, i.e., the features of a latent IBD [ 87 , 100 , 166 ]. Indeed, there is a case report of a patient with psoriasis who developed clinical CD after up to 15 years since diagnosis of the primary condition.…”
Section: Resultsmentioning
confidence: 99%
“…Juzlova et al. 2016 described that positivity for ASCA preceded clinical manifestation by approximately 38 months in 10 out of 32 psoriatic patients with Crohn’s disease (31%) [ 142 ]. The association between psoriasis and IBD has been reinforced by the finding that one can appear as a paradoxical adverse event of the treatment for the other, as discussed later [ 143 145 ].…”
Section: The Clinical Link Between Psoriasis and Ibd: Since Both Dise...mentioning
confidence: 99%
“…Latent IBD features, such as elevated levels of anti-Saccharomyces cerevisiae antibodies (ASCA), may precede the manifestation of IBD in patients with psoriasis. Juzlova et al 2016 described that positivity for ASCA preceded clinical manifestation by approximately 38 months in 10 out of 32 psoriatic patients with Crohn's disease (31%) [142]. The association between psoriasis and IBD has been reinforced by the finding that one can appear as a paradoxical adverse event of the treatment for the other, as discussed later [143][144][145].…”
Section: The Clinical Link Between Psoriasis and Ibd: Since Both Dise...mentioning
confidence: 99%